Psychological characteristics of adolescents with diseases of the endocrine system - Narmetova Yulduz Karimovna; Juraeva Dildora Nasirdinovna; Dilshodova Madinabonu Rustam kizi; Mansurova Yulduz Jamshid kizi; Zavaruyeva Tatyana Igorevna (The Bioscan, 2024)
This article discusses the psychological characteristics of adolescents with endocrine system diseases, the functions of the endocrine system, disorders and factors affecting hormones, diseases caused by hormone dysfunction, the course of these diseases in adolescents, their conditions, the consequences of diseases, and their impact on cognitive processes. Information about the effects is provided.